Failure analysis : a practical guide for manufacturers of electronic components and systems - Bazu, M. I. (Marius I.), 1948-; Bajenescu, Titu I., 1938- (Chichester, West Sussex, U.K. : John Wiley & Sons, 2011)
'Manufacturers of electronic components, devices, ICs and electronic systems, also reliability testing engineers and managers in this area'--
Includes bibliographical references and index.
Keywords: Electronic apparatus and appliances -- Reliability; Electronic systems -- Testing; System failures (Engineering) -- Prevention